2018
DOI: 10.1186/s12920-018-0380-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic risk variants and glucose intolerance during pregnancy in north Indian women

Abstract: BackgroundGestational diabetes (GDM) is a more common problem in India than in many other parts of the world but it is not known whether this is due to unique environmental factors or a unique genetic background. To address this question we examined whether the same genetic variants associated with GDM and Type 2 Diabetes (T2D) in Caucasians also were associated with GDM in North Indian women.MethodsFive thousand one hundred pregnant women of gestational age 24–28 weeks from Punjab were studied by a 75 g oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The power to detect association of rs11605924 ( CRY2 ) with GDM at a significance level of 0.05 was 0.85. This protective effect was consistent even when WHO 1999 criteria were applied in our previous study on the same population . CRY2 encodes the circadian rhythm gene cryptochrome 2 and is a target for the CLOCK ‐ BMAL1 , which are core components of the endogenous clock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The power to detect association of rs11605924 ( CRY2 ) with GDM at a significance level of 0.05 was 0.85. This protective effect was consistent even when WHO 1999 criteria were applied in our previous study on the same population . CRY2 encodes the circadian rhythm gene cryptochrome 2 and is a target for the CLOCK ‐ BMAL1 , which are core components of the endogenous clock.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we observed that the T2D risk SNP in the TCF7L2 gene did not associate with GDM using either WHO 1999 or WHO 2013 criteria . However, using the Swedish GDM diagnostic criteria (2‐h capillary blood glucose concentration ≥ 10 mmol L −1 ), we see a trend towards an association.…”
Section: Discussionmentioning
confidence: 99%
“…A woman with GDM is at increased risk of GDM during subsequent pregnancies as well as increased risk ofT2D . There is also emerging evidence for shared genetic background of GDM and T2D . Similar to T2D, GDM can also be heterogeneous, especially in different ethnic groups .…”
Section: Gestational Diabetes and Intrauterine Programmingmentioning
confidence: 99%
“…Therefore, the disruption of Grb14‐mediated homeostasis may be associated with the progression of several physiological disorders. Genetic analyses during the last decade, including genome‐wide association studies, have demonstrated that the GRB14 gene is associated with cancer, obesity, and metabolic diseases such as noninsulin‐dependent and gestational diabetes mellitus …”
Section: Introductionmentioning
confidence: 99%
“…Genetic analyses during the last decade, including genome-wide association studies, have demonstrated that the GRB14 gene is associated with cancer, obesity, and metabolic diseases such as noninsulin-dependent and gestational diabetes mellitus. [11][12][13][14][15][16][17][18] The Grb7 family proteins is composed of several modular signaling domains, including N-terminal polyproline sequences, a Rasassociation domain, a pleckstrin homology (PH) domain, and a Cterminal Src homology-2 (SH2) domain. In addition, Grb7 family proteins contain a unique region termed the between PH and SH2 (BPS) domain 8 or phosphorylated IR-interacting region (PIR).…”
Section: Introductionmentioning
confidence: 99%